Effectiveness of Telemedicine Interventions In Diabetes Management At Primary Care Settings In Asia: A Systematic Review Protocol - Das, Amity; Kaushal, Pawna; Agarwal, Disha; Sharma, Megha (National Journal of Community Medicine, 2021)
Background: This systematic review will focus on the effectiveness of Telemedicine interventions on diabetic management at primary care settings in Asia. The objectives of this systematic review and meta-analysis are to synthesize the clinical effectiveness and to compare the effectiveness of Telemedicine interventions in the diabetes management in Asia. Methodology: The conducting and reporting of this review will adhere to the PRISMA guidelines. The search strategy will include MeSH terms related to Diabetes, Telemedicine, Diabetic management, Primary Healthcare, Effectiveness, and Asia to find relevant studies. Other synonymous words will be searched using Boolean operator “AND”/”OR” on PUBMED, EMBASE, SCOPUS, COCHRANE. Randomized controlled trials examining the effectiveness of telemedicine interventions in the management of Diabetes Mellitus patients at Primary Care settings in Asia will be included. A random effects meta-analysis will be conducted with the REVMAN software version 5.3.5. Cumulative and comparative meta-analysis will be done with STATA software version SE16. Discussion: This review and meta-analysis will be among the first to give an extensive purview on the effectiveness of telemedicine in diabetes management at Primary Care settings in Asian population. Systematic review registration: The protocol has been registered at the International Prospective Register of Systematic Reviews (PROSPERO registration number: 42021210002).